2018
DOI: 10.3389/fmicb.2018.02946
|View full text |Cite|
|
Sign up to set email alerts
|

Whole Genome Sequencing of Australian Candida glabrata Isolates Reveals Genetic Diversity and Novel Sequence Types

Abstract: Candida glabrata is a pathogen with reduced susceptibility to azoles and echinocandins. Analysis by traditional multilocus sequence typing (MLST) has recognized an increasing number of sequence types (STs), which vary with geography. Little is known about STs of C. glabrata in Australia. Here, we utilized whole genome sequencing (WGS) to study the genetic diversity of 51 Australian C. glabrata isolates and sought associations between STs over two time periods (2002–2004, 2010–2017), and with susceptibility to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 48 publications
(76 reference statements)
4
21
0
Order By: Relevance
“…Altogether, this supports that echinocandin resistance cannot be explained by MSH2 mutator phenotype, as previously reported (Delliere et al, 2016; Healey et al, 2016a; Biswas et al, 2018; Byun et al, 2018; Hou et al, 2018; Singh et al, 2018; Bordallo-Cardona et al, 2019). Likewise, no clear association between MSH2 sequence and increased fluconazole resistance or genotypes was detected on these isolates either (Biswas et al, 2018; Bordallo-Cardona et al, 2019), although a correlation with specific genetic types was previously described (Delliere et al, 2016; Byun et al, 2018; Hou et al, 2018). These results confirm that MSH2 substitutions may be constitutive variations from the gene rather than resistance-related or genotype-related mutations (Carrete et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Altogether, this supports that echinocandin resistance cannot be explained by MSH2 mutator phenotype, as previously reported (Delliere et al, 2016; Healey et al, 2016a; Biswas et al, 2018; Byun et al, 2018; Hou et al, 2018; Singh et al, 2018; Bordallo-Cardona et al, 2019). Likewise, no clear association between MSH2 sequence and increased fluconazole resistance or genotypes was detected on these isolates either (Biswas et al, 2018; Bordallo-Cardona et al, 2019), although a correlation with specific genetic types was previously described (Delliere et al, 2016; Byun et al, 2018; Hou et al, 2018). These results confirm that MSH2 substitutions may be constitutive variations from the gene rather than resistance-related or genotype-related mutations (Carrete et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Isolates from the same patient seemed to have a clonal origin by using these two typing techniques, although the use of next generation sequencing in order to compare their genomes would be necessary to prove if they are isogenic. The most frequent genotype among these patients was ST3, which has been reported as one of the most prevalent STs worldwide (Dodgson et al, 2003; Lott et al, 2012; Hou et al, 2017; Biswas et al, 2018; Byun et al, 2018; Mushi et al, 2018). No association between echinocandin resistance development and genetic type was found, which was in agreement with other reports (Dodgson et al, 2003; Abbes et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with several recent clinical studies that did not see an association between MSH2 genotype and prevalence of drug resistance in C. glabrata (2729, 61, 62). However, in our previous study, we found that several MSH2 variants, including MSH2 E231G/L269F , when introduced on a plasmid into an ATCC 2001-derived msh2Δ mutant, did not fully rescue that strain’s elevated mutation rate (24).…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, in Cryptococcus , naturally occurring mutations in MSH2 have been shown to contribute to microevolution and population diversity (59, 60). Yet, recent clinical studies have not found an association between specific MSH2 alleles and drug resistance (2729, 61, 62), raising the question of whether clinical isolates carrying these alleles are true mutators. To answer this question, it is necessary to measure and directly compare mutation rates between clinical isolates of C.…”
Section: Introductionmentioning
confidence: 99%
“…NGS further has potential to detect novel mutations implicated in phenotypic resistance that may otherwise be missed by targeted DNA sequencing. In C. glabrata, NGS has detected multiple SNPs in CgPDR1 and CgCDR1 in azoleresistant isolates; although none were definitively associated with resistance, azole-resistant isolates tended to have amino substitutions in pdr1 beyond the first 250 amino acid positions, unlike the susceptible isolates (Biswas et al, 2018). The cost of NGS is currently ∼AUD 80/sample (∼USD 57) but this is likely to fall with technological advances allowing ease of use for routine applications.…”
Section: Molecular Methods To Detect Azole Resistance In Candida Speciesmentioning
confidence: 99%